Congenital peritoneal band causing bowel ischaemia post caesarean section: a rare occurrence - Phon, SE; Ng, Beng Kwang; Ng, WYL; Rahman RA; Zainuddin AA; Mahdy ZA (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Congenital peritoneal band is an extremely rare condition, but may induce small bowel obstruction (SBO) at any age, predominantly in childhood and rarely in adults. We report a case of extensive bowel ischaemia following caesarean section, due to trapping of an intestinal loop between a congenital peritoneal band and the mesentery. A 42-year-old, Gravida 2 Para 1, who has no history of prior abdominal surgery or trauma, presented in spontaneous labour and underwent an uncomplicated emergency lower segment caesarean section, for fetal distress. Postoperatively, she had worsening abdominal distension and pain, followed by vomiting. Computed Tomography Scan of the abdomen showed gross fluid retention with marked small bowel dilatation and fluid filled bowel loops. An emergency exploratory laparotomy was performed which revealed a congenital band, extending between the right fimbrial end and the small bowel mesentery, looping over the small bowel, causing extensive small bowel ischemia. Postoperative course was uneventful. In conclusion, congenital peritoneal band causing small bowel obstruction, although rare, should be considered in the differential, especially for patients with virgin abdomen.